PENGARUH HORMON TIROKSIN (T4) TERHADAP PERTUMBUHAN BERAT BADAN TIKUS (Rattus norvegicus) GALUR WISTAR - , LUSSYA EVELINE R ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Thyroxine influences animal growth because it has an effect on the carbohydrates, fats, and vitamins metabolism